O Instituto Histórico e Geográfico de Minas Gerais e a escrita da história do Brasil republicano - Mariana Vargens Silva (2017)
The implantation of the republican regime in Brazil encouraged the rewriting of the national history, a movement coordinated by the Instituto Histórico e Geográfico Brasileiro, which made efforts to gather around itself the regional institutes, including the Instituto Histórico e Geográfico de Minas Gerais, founded in 1907. The members of the Instituto Mineiro faced the challenge of creating a discourse that was at the same time capable of bringing together its internal political elite, reducing regional conflicts, and projecting the state into national history. To this end, they have selected in the past some themes that were worked in a recurrent way: the action of the bandeirantes paulistas that supposedly had populated the territory and initiated the civilization in Minas; the Revolta de Felipe dos Santos, from 1720, a movement that was forerunner of the great Inconfidência Mineira, which was specially addressed as a representative of the state's participation in the formation of the national Republic. The way in which history was written was also rethought in the period, paying attention to both the new European proposals and the demands placed by the new political regime